Cell death of human colon cancer cells, induced by adociaquinone B from A marine sponge and a compound from Annona squamosa Linn - Mazahery, Ahmad Reza F. (Quezon City College of Science, University of the Philippines, 2006)
Apoptosis, a less inflammatory mode of cell death, has been the recent focus of many researchers on cancer chemotherapy. The compound adociaquinone B, taken from the marine sponge Xestospongia sp., and a TLC-pure compound from the leaf extracts of A.squamosa Linn, were screened from their (DAPI) nuclear straining revealed that cells treated with either compound developed membrane blebs and condensed nuclei, which is typical among apoptotic cells. The percentage of apoptotic Col2 cells treated with A. squamosal Linn compound at 50ug/ml dramatically increased by about 50% 12 hours post- treatment; while the percentage of apoptotic Col2 cells treated with adociaquinone B at 2.3ug/ml dramatically increased by 70% 12 hours post-treatment. Terminal deoxynucleotidytransferase-mediated dUTP nick end label (TUNEL) straining revealed that apoptosis in Col2 cells, treated with either compound, involved DNA fragmentation. Using a colorimetric assay kit, the caspase 3 activity of Col2 cells treated with 50 ug/ml A. squamosa Linn after 12 hours, was computed at 5.54x10-3 uM pNA released/ug protein. No caspase 3 activity, however, was observed for adociaquinone B-treatedsuggesting that the compound induces apoptosis in a caspase 3-independent fashion. Caspase 3 is the effector enzyme released during apoptosis which includes DNA fragmentation and breaking up of cells into small membrane-bounded apoptotic bodies. In Col2 cells, immunoblotting revealed that no Bcl2 cells, protein could be seen in either untreated or treated cells, as indicated by the lack of a28kDa protein band, which is the estimated weight of the Bcl2 protein. However, a protein band of about 50kDa was resolved in the same blot, and its expression appeared to be decreased in amount in apoptotic cells. Based on all the assays conducted, both compounds were able to induce an apoptotic mode of cell death, making them potential cancer chemotherapeutic agents.
Vita.
Thesis (M.S. Biology)--University of the Philippines Diliman
Keywords: Cancer -- Treatment; Cancer cells -- Human colon